Omega-3 Fatty Acids in Cardiovascular Health: Navigating the Duality of Benefits and Risks - Shah, Priyanshi; Shah, Twinkle; Srinivas, Pathan Mayur; Gupta, Vasu; Ruhela, Namita; Jain, Rohit (Eastern Journal of Medical Sciences, 2025)
Objective: Cardiovascular diseases (CVDs) remain the leading global cause of death and healthcare economic burden. Omega-3 fatty acids (FAs) have been widely advocated for their potential role in improving cardiovascular health, yet emerging evidence questions their efficacy across diverse CVD contexts. This narrative review evaluates the historical and current understanding of omega-3 FAs in CVD management, contrasting their purported benefits with contemporary evidence on risks and outcomes. Methods: We conducted a comprehensive synthesis of existing literature, including clinical trials, meta-analyses, and observational studies, to assess the role of omega-3 FAs in primary and secondary CVD prevention. Focus was placed on their effects on hypertension, atherosclerosis, ischemic heart disease, and overall morbidity/mortality. Results: Omega-3 FAs demonstrate clear benefits in secondary prevention of certain CVDs, particularly in reducing triglycerides and arrhythmia risk. However, recent studies highlight inconsistent outcomes regarding their impact on overall mortality, stroke prevention, and efficacy in diverse populations. While some trials reaffirm their anti-inflammatory and plaque-stabilizing properties, others suggest negligible effects or even potential risks (e.g., atrial fibrillation in high doses). Conclusion: The role of omega-3 FAs in CVD management is nuanced, with evidence supporting selective benefits but also underscoring limitations and unresolved controversies. Clinicians must weigh these findings against individual patient profiles. Further research is needed to clarify optimal dosing, formulations, and target populations to maximize therapeutic potential while mitigating risks.